2021
DOI: 10.1186/s12903-021-01512-4
|View full text |Cite
|
Sign up to set email alerts
|

Glide path enlargement of curved molar canals using HyFlex EDM glide path file versus PathFile: a comparative study of preparation time and postoperative pain

Abstract: Background This randomized clinical trial aimed to compare the preparation time and severity of postoperative pain between HyFlex Electric Discharge Machine (EDM) glide path file (GPF) and PathFile. Methods Eighty patients whose molar teeth had at least one severely curved canal were treated by the same specialist. After access cavity preparation, the patients were randomly assigned to receive glide path enlargement with either HyFlex EDM GPF or Pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…EDM is a non-contact thermal erosion process used to machine electrically conductive materials by means of precisely controlled electrical discharges. 16 According to the results in this study, the null hypothesis could be rejected. As statistically significant differences in the cyclic fatigue resistance were observed among the three evaluated files.…”
Section: Resultsmentioning
confidence: 77%
“…EDM is a non-contact thermal erosion process used to machine electrically conductive materials by means of precisely controlled electrical discharges. 16 According to the results in this study, the null hypothesis could be rejected. As statistically significant differences in the cyclic fatigue resistance were observed among the three evaluated files.…”
Section: Resultsmentioning
confidence: 77%
“…The authors are unaware of any other study comparing the preparation times of these two files in order to compare results. Previous studies showed that rotary glide path files need less time than manual K-files [ 22 , 26 , 27 , 28 ], and single file systems for glide path preparation are faster than multiple instrument file systems [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the achieved articles, 8 articles were excluded [14,[19][20][21][22][23] since two studies were systematic review [19,21]. One study was an in vitro study which didn't follow the selection parameter and was excluded [14] and the remaining though being in vivo studies [20,22,23] were still not selected since the studies did not follow the strict selection parameters set for this review. Finally, four studies were selected to be included for this review [6][7][8][9].…”
Section: ) Selection Criteria For the Studiesmentioning
confidence: 99%